Comparing Retreatments and Expenditures in Flow Diversion Versus Coiling for Unruptured Intracranial Aneurysm Treatment: A Retrospective Cohort Study Using a Real-World National Database. Issue 1 (20th September 2019) - Fukuda, Haruhisa; Sato, Daisuke; Kato, Yoriko; Tsuruta, Wataro; Katsumata, Masahiro; Hosoo, Hisayuki; Matsumaru, Yuji; Yamamoto, Tetsuya
Abstract: BACKGROUND: Flow diverters (FDs) have marked the beginning of innovations in the endovascular treatment of large unruptured intracranial aneurysms, but no multi-institutional studies have been conducted on these devices from both the clinical and economic perspectives. OBJECTIVE: To compare retreatment rates and healthcare expenditures between FDs and conventional coiling-based treatments in all eligible cases in Japan. METHODS: We identified patients who had undergone endovascular treatments during the study period (October 2015-March 2018) from a national-level claims database. The outcome measures were retreatment rates and 1-yr total healthcare expenditures, which were compared among patients who had undergone FD, coiling, and stent-assisted coiling (SAC) treatments. The coiling and SAC groups were further categorized according to the number of coils used. Retreatment rates were analyzed using Cox proportional hazards models, and total expenditures were analyzed using multilevel mixed-effects generalized linear models. RESULTS: The study sample comprised 512 FD patients, 1499 coiling patients, and 711 SAC patients. The coiling groups with ≥10 coils and ≥9 coils had significantly higher retreatment rates than the FD group with hazard ratios of 2.75 (1.30-5.82) and 2.52 (1.24-5.09), respectively. In addition, the coiling group with ≥10 coils and SAC group with ≥10 coils had significantly higher 1-year expenditures than the FD group with cost ratios (95% CI) of 1.30 (1.13-1.49) and 1.31 (1.15-1.50), respectively. CONCLUSION: In this national-level study, FDs demonstrated significantly lower retreatment rates and total expenditures than conventional coiling with ≥ 9 coils.